"Between the Flash and Fall of Turning": "New York" School Poets, American Pragmatism, and the Construction of Subjectivity - Schnier, Zachariah (Université d'Ottawa / University of Ottawa, 2014)
With my dissertation entitled “Between the Flash and Fall of Turning”: “New York” School Poets, American Pragmatism and the Construction of Identity, I seek to account for the depiction of the anti-foundational self which emerges time and again in the poetry of John Ashbery, Frank O’Hara, Barbara Guest, James Schuyler and Kenneth Koch. While theorizing the self as a contingent, provisional, and shifting construct is hardly new to a theoretically oriented academy transiting into the present century, scholars and critics have tended to ground such interpretations in “structural linguistics” and so-called “French philosophy.” One of the goals of this project, therefore, is to propose that the philosophical skepticism toward the self as a site of stable and enduring meaning has always been felt and articulated by American Pragmatism, specifically in the writings of Ralph Waldo Emerson, William James and John Dewey. While a handful of critics have looked to Pragmatism to account for the protean self in the work of “New York” School Poets, these commentators have tended to focus their attention largely on O’Hara’s and Ashbery’s poetry. This project seeks, on the one hand, to round out this work with close readings of all the major “New York” School Poets, and extend it, on the other, by looking beyond poetry to visual art and classroom pedagogy to examine evidence of a Pragmatist orientation across the disciplines, despite the apparent interpretive consensus that American Pragmatism “goes silent” at mid-century.
Keywords: Poetry; Pragmatism; Subjectivity; New York; Cold War